Comparison of T2N0M0 and T3aN0M0 in Predicting the Prognosis of Patients With Renal Cell Carcinoma - He, Xiaobo; Mao, Xiaopeng; Li, Jibin; Guo, Shengjie (Frontiers in Oncology, 2020)
Background: To investigate the prognostic role of tumor size in patients with pathological T2N0M0 and T3aN0M0 renal cell carcinoma (RCC) treated by radical surgery. Methods: A total of 3,662 cases were retrospectively analyzed from the Surveillance, Epidemiology and End Results (SEER) from 2010 to 2012. Overall survival (OS) and cancer-specific survival (CSS) data were obtained. The log-rank test was used to compare survival distributions and Cox proportional hazards model was used for univariate and multivariate analyses, respectively. Results: In the low-risk T3aN0M0 (perinephric fatty infiltration or sinus fatty infiltration only) group, patients with tumor size ≤ 7 cm were associated with a better OS (P = 0.009) and CSS (P < 0.001) than those with tumor size >7 cm. However, there was no difference in OS (P = 0.129) and CSS (P = 0.539) between T2bN0M0 patients and low-risk T3aN0M0 patients with tumor size ≤ 7 cm. A new T classification grouping patients with both T2bN0M0 and T3aN0M0 with tumor diameter ≤ 7 cm into the same staging category (pT2aN0M0, pT2bN0M0+low-risk pT3aN0M0 [tumor diameter ≤ 7cm], low-risk pT3aN0M0 [tumor diameter >7 cm], high-risk pT3aN0M0) was proposed and it was found as an independent predictive variable for OS and CSS. Conclusions: Findings from the present study suggest that the reclassification of pT2N0M0 and pT3aN0M0 RCC can lead to better prediction of OS and CSS.